Radar and Electronic Warfare Principles for the Non-Specialist - Hannen, Paul J. (SciTech Publishing, 2013)
This enhanced and fully revised fourth edition of Radar and Electronic Warfare Principles for the Non-specialist includes five all new sections on electronic warfare and its relationship with radar systems and distills the very complex technologies of radar and electronic warfare into their fundamentals, tying them to the laws of nature on one end and to the most modern and complex systems on the other